2018
DOI: 10.1002/ijgo.12684
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in delivery and performance of a cervical cancer prevention program in the Kurdistan Region of the Iraq health system

Abstract: Objective To investigate health‐system challenges responsible for the poor performance of a cervical cancer prevention program in the Kurdistan Region of Iraq. Method A qualitative study was conducted among a purposive sample of healthcare providers and female volunteers in Erbil, Kurdistan Region of Iraq, between December 10, 2014, and July 23, 2016. Data were collected from participants using in‐depth semi‐structured interviews. The interviews were then transcribed and analyzed with an inductive content anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…However, the results of the present study suggest that the cultural acceptability of HPV testing/screening for women in Iraq has yet to be determined. Personal embarrassment and humility may lead to non-disclosure of signs and symptoms ( Ali et al, 2017 ; Rasul et al, 2019 ). Modesty and reticence are social characteristics expected of women when discussing or visualizing the female body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of the present study suggest that the cultural acceptability of HPV testing/screening for women in Iraq has yet to be determined. Personal embarrassment and humility may lead to non-disclosure of signs and symptoms ( Ali et al, 2017 ; Rasul et al, 2019 ). Modesty and reticence are social characteristics expected of women when discussing or visualizing the female body.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of nurses performing smears/HPV is not well established ( Ali et al, 2021 ; Ali, Skirton, Clark, & Donaldson, 2017 ). Previous studies have indicated the necessity for nurses to be adequately informed of HPV testing ( Rasul, Moghdam, Karim, & Cheraghi, 2019 ; Kolutek, & Avci, 2014 ; Wilson et al ., 2016 ). The Global Advisory Panel on the Future of Nursing (GAP-FON) was introduced in November 2016 with the goal of encouraging global nursing collaboration and enhancing global health ( Wilson et al ., 2016 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to studies by Ahmad and Almeida and those performed in North Korea and European countries, today the evaluation of the performance indicators of preventable cancer screening programs for optimal implementation is considered as the best preventive and costbenefit measure (17,(19)(20)(21). Many studies in several countries showed higher rates of mortality from cervical cancer due to the lack of screening resources (8).…”
Section: Discussionmentioning
confidence: 99%
“…ing program and evaluation of its performance indicators based on individuals' health status, disease burden, and the cost of current screening methods, as well as cultural, economic, and social considerations minimize the adverse effects of screening and maximize its benefits (17,18). In the study by von Karsa et al (7) (7,17,20,21).…”
Section: Introductionmentioning
confidence: 99%